2011
DOI: 10.1371/journal.pone.0023414
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of PI3K/Akt/GSK3β in Motoneuron Specification from Human Neural Stem Cells in Response to FGF2 and EGF

Abstract: Fibroblast growth factor (FGF) and epidermal growth factor (EGF) are critical for the development of the nervous system. We previously discovered that FGF2 and EGF had opposite effects on motor neuron differentiation from human fetal neural stem cells (hNSCs), but the underlying mechanisms remain unclear. Here, we show that FGF2 and EGF differentially affect the temporal patterns of Akt and glycogen synthase kinase 3 beta (GSK3β) activation. High levels of phosphatidylinositol 3-kinase (PI3K)/Akt activation ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 46 publications
4
55
0
Order By: Relevance
“…Consistent with our observation of reduced expression of phospho-defective HLXB9 in ␤-cells, in human fetal neural stem cells inhibition of PI3K/AKT or overexpression of active GSK-3␤ increased HLXB9 mRNA and protein expression (31), implicating that GSK-3␤-mediated phosphorylation could promote pHLXB9 stability. Also, decreased HLXB9 expression corelated with the presence of the inactive form of GSK-3␤ (31).…”
Section: Gsk-3␤-mediated Phosphorylation Regulates Hlxb9supporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with our observation of reduced expression of phospho-defective HLXB9 in ␤-cells, in human fetal neural stem cells inhibition of PI3K/AKT or overexpression of active GSK-3␤ increased HLXB9 mRNA and protein expression (31), implicating that GSK-3␤-mediated phosphorylation could promote pHLXB9 stability. Also, decreased HLXB9 expression corelated with the presence of the inactive form of GSK-3␤ (31).…”
Section: Gsk-3␤-mediated Phosphorylation Regulates Hlxb9supporting
confidence: 90%
“…Also, decreased HLXB9 expression corelated with the presence of the inactive form of GSK-3␤ (31). Whether HLXB9 is phosphorylated on Ser-78/ Ser-80 in neural stem cells or in other cell types remains to be determined.…”
Section: Gsk-3␤-mediated Phosphorylation Regulates Hlxb9mentioning
confidence: 99%
“…Due to its essential role in cell survival, the PI3K/Akt pathway and inositol phosphatases that regulate it are proposed to play a role in stem cell self-renewal, maintenance, and differentiation. This includes several types of stem cells, including pluripotent stem cells, [31,[62][63][64][65] HSC, [20,22,[66][67][68] neural stem cells [69][70][71][72][73][74], and epithelial stem cells [75]. A recurring theme in several stem cell types is for the PI3K/Akt pathway to inactivate GSK3b thus promoting activation and nuclear translocation of b-catenin [76,77].…”
Section: Discussionmentioning
confidence: 99%
“…Although these pathways have not previously been linked to neuromuscular pathology in SMA, β-catenin signaling pathways are known to play an important role in regulating motor neuron differentiation and stability, including regulating synaptic structure and function (42)(43)(44). Interestingly, Li and colleagues previously reported that motor neuron differentiation is regulated by retrograde signaling through β-catenin from skeletal muscle (43).…”
Section: Micementioning
confidence: 99%